The Christchurch earthquake: lessons from the real-life experiences of early childhood teachers: Special Issue: 'Preparing Early Childhood Teachers to Assist Children Who Are Caught in Disasters'. Issue 4 (1st October 2020) - Bateman, Amanda; Robinson, Paula
ABSTRACT: ven though natural disasters are becoming increasingly prevalent, research investigating and offering practical advice to teachers around caring for children during and after an earthquake event is limited. This article aims to provide unique insight from early childhood teachers into a real-life experience of caring for children at their early childhood center during and after the earthquake in Christchurch New Zealand in February 2011. Details of the setting on the day of the earthquake prior to the event are discussed, followed by what happened during the earthquake, the situation immediately following the earthquake when parents arrived to collect their children, and the subsequent days and weeks following the earthquake. The article concludes with advice and guidance from the teachers around tips and strategies for supporting children's social and emotional wellbeing in such a situation for fellow teachers who may find themselves in similar circumstances in the future. Through providing this discussion, future early childhood teachers can be guided, not by hypothetical best practice, but by real-life events from early childhood teachers who have first-hand experience of supporting children prior to, during and after an earthquake event. This therefore provides essential opportunities for learning from practice and preparing for the future.